The Evolution of the Concept of Prison in Viktor Pelevin’s Works - Čenys, Tomas (Literatūra, 2023)
This article describes the evolution of the concept of the prison in the texts of Victor Pelevin. The prison image changes throughout the author’s works, and the article compares his early stories The Yellow Arrow and Hermit and Six-Toes with his later story Stolypin. The article describes the evolution of the paired heroes as well of the stories: the student and the teacher. Using the evolution of the heroes as a model, the article shows how in Pelevin’s early stories the prison becomes a place from which one can escape, a metaphor for Soviet and post-Soviet society of the 90s, and the heroes of early Pelevin are able to escape with the help of their connection to culture and clues scattered in the surrounding world. The heroes of the story Stolypin – oligarchs, in spite of staying within the same student–teacher paradigm, represent a deconstruction of their predecessors, devoid of any interests other than mercantile ones, and in many ways parody the heroes of The Yellow Arrow and Hermit and the Six-Toes. The image of the prison wagon from the story Stolypin is a metaphor for modern Russia.